METHOD OF DISPLAYING AN EXECUTABLE BUSINESS PROCESS MODELS INTO PETRI NETS - Igor G. Fedorov (Статистика и экономика)
Executable business process models, as well as programs, require evidence of a defect-free finish. The methods based on the formalism of Petri nets are widely used. A business process is a network of dishes, and its properties are set by the analysis of the properties of the network. The aim is to study the methods of displaying an executable business process model in a Petri net. Analysis of the properties of the resulting model allows us to prove a number of important properties: it is a network of free choice and clean without looping.